The problem of psychological conflicts in inclusive rehabilitation institutions and ways to solve them - Anishchenko, M. A.; Myrna, A. I.; Myrnyi, D. P.; Myrnyi, S. P.; Pushchyna, I. V.; Mosaiev, Y. V.; Аніщенко, Михайло Анатолійович; Мирний, Сергій Петрович (My University, 2021)
The article examines the features of the application of various technologies for the prevention and resolution of psychological conflicts in inclusive rehabilitation institutions. The article considers the general features of conflicts that may arise during the rehabilitation process, taking into account the nosologies of patients, gender differences of persons in need of social, medical and psychological rehabilitation. The article actualizes the issue of psychological conflicts in rehabilitation institutions as this problem is not clarified features of internal personal and interpersonal conflicts in the rehabilitation process. The urgency of gender- based violence in the process of rehabilitation and its relationship with sexual violence, the problem of which is increasingly discussed in all spheres of society, are considered. Recommendations for the prevention and resolution of gender conflicts in the rehabilitation process are offered. The problems of the emergence and resolution of religious conflicts that may arise due to ignoring the religious needs of persons undergoing rehabilitation have been studied. The team of authors proposed to build models of conflict resolution in the rehabilitation process through mediation, prevention and treatment of compulsive disorders and diseases and the prospects of cognitive and gestalt psychology in the field of conflict resolution in rehabilitation institutions. The text analyzes the Japanese national experience in resolving conflicts within enterprises and extrapolates it to the sphere of conflicts that may arise in the rehabilitation process in specialized institutions.
Keywords: psychological conflicts; modeling; prevention of conflict situations; resolution of psychological conflicts in inclusive institutions; rehabilitation institutions